2018
DOI: 10.17116/kurort201895258-64
|View full text |Cite
|
Sign up to set email alerts
|

The application of kinesiotaping for the rehabilitation of the post-stroke patients

Abstract: This review of the scientific literature was designed to consider the prospects for the application of kinesiotaping for the rehabilitation of the post-stroke patients. The relevance of the work arises from the absence of a systemic analysis of the large number of investigations that have been carried out during the past two years. The objective of the present review article was to evaluate the influence of kinesiotaping on the health status of the post-stroke patients and the course of their rehabilitative tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…Some scholars have conducted longitudinal studies on some anisotropy values and found that with the recovery of stroke, the anisotropy value of the affected cortical spinal cord gradually increases, and its subsequent functional recovery is also good [21]- [23]. In short, before Studies have suggested that there is a positive correlation between partial anisotropy of cortical spinal tract and motor function recovery in patients with motor dysfunction after stroke [24]. At present, there are many comparative studies on the brain structure and function of normal people in high-altitude and low-altitude areas using magnetic resonance imaging [25], [26], and researches on patients have focused on epidemiology, pathophysiology, neurochemistry, etiology And for the diagnosis and treatment of the disease [27]- [29], there are relatively few studies on neuroimaging.…”
Section: Introductionmentioning
confidence: 99%
“…Some scholars have conducted longitudinal studies on some anisotropy values and found that with the recovery of stroke, the anisotropy value of the affected cortical spinal cord gradually increases, and its subsequent functional recovery is also good [21]- [23]. In short, before Studies have suggested that there is a positive correlation between partial anisotropy of cortical spinal tract and motor function recovery in patients with motor dysfunction after stroke [24]. At present, there are many comparative studies on the brain structure and function of normal people in high-altitude and low-altitude areas using magnetic resonance imaging [25], [26], and researches on patients have focused on epidemiology, pathophysiology, neurochemistry, etiology And for the diagnosis and treatment of the disease [27]- [29], there are relatively few studies on neuroimaging.…”
Section: Introductionmentioning
confidence: 99%